Full of your glory liturgy, cosmos, creation : papers from the 5th Yale ISM Liturgy Conference, June 18-21, 2018 - Berger, Teresa 1956- (Liturgical Press Academic, 2019)
"A collection of essays exploring the intersections between the world of liturgy and the worlds of creation and the cosmos. The essays were first presented at the 2018 Yale Institute of Sacred Music Liturgy Conference"--
Keywords: Geschichte; Liturgie; Liturgik; Liturgics / Congresses; Creation / Congresses; Creation; Liturgics; Conference papers and proceedings; Konferenzschrift -- 5th Yale ISM liturgy conference -- 18.06.2018-21.06.2018 -- New Haven, CT